Emergency peripartum hysterectomy: our experience. (November 2016) - Tahaoglu, A.; Balsak, D.; Togrul, C.; Obut, M.; Tosun, O.; Cavus, Y.; Bademkiran, H.; Budak, S.
Abstract Purpose To investigate the incidence of and reasons for emergency peripartum hysterectomy (EPH) between 2009 and 2013 in our hospital, one of the three hospitals with the highest rates of delivery in Turkey. Methods A retrospective study. Seventy-six peripartum hysterectomies were evaluated. We compared the modes of delivery and examined whether bilateral internal iliac artery ligation was performed. Results The incidence of EPH was 0.77 in 1000. The majority of cases involved multiparity, uterine rupture, placenta praevia, or placental invasion abnormalities. The most frequent reason for EPH was uterine atony (64.5 %). There was no statistically significant relationship with mode of delivery; however, the complication rate and requirement for fresh frozen plasma were significantly (p  < 0.01) related to whether bilateral internal iliac artery ligation was performed. Conclusion Uterine atony was the most common indication for EPH. The most important step to avoid performing EPH is to calculate patients' risks for postpartum bleeding. Postpartum haemorrhage may not be preventable, but when it happens, obstetricians must be prepared to perform EPH, and in high-risk patients, to perform internal iliac artery ligation.